AGIHAN WILAYAH LONGSOR DI DAS JENELATA SUB DAS JENEBERANG KABUPATEN GOWA - Samad, Nurmadania; Zhiddiq, Sulaiman; Uca, Uca (Jurnal Environmental Science, 2020)
This study aims to agihan the landslide hazard of Jenelata watershed, Jeneberang Sub-watershed, Gowa Regency. This type of research is quantitative research with a descriptive approach. Using the land unit analysis results of the overlay of two maps, namely the slope map, land shape, soil type and land use, so that 41 units of land were obtained. The sampling technique used in this study is based on land units. Sampling was carried out in nine land units which were the result of overlays from the land slope map and soil type map. The results showed that the Jenelata watershed sub-Jeneberang watershed Guat Kabuaten is a moderate level of vulnerability that is divided in each village, in part in pattallikang village, partly in Bontomanai village, part in mangempang village, part in tassese village, part in Jenebatu village sicini village, partly in parang lompoa village, partly in sapaya village, and paladingang. The level of landslide hazard of Das Jenelata Sub-Jeneberang sub-watershed is dominated by moderate danger level with a total score of 2.34 - 3.67. Jenelata Watershed Sub Das Jeneberang Gowa Kabuaten for its longitudinal vulnerability level is divided into two areas, namely low and medium areas.